Properties of Asphalt Concrete while Applying Bitumen Capsuled in Poly-Ethylene Shell - V. N. Romaniuk (Наука и техника)
The paper presents test results of asphalt concrete samples which have been obtained with the help of new technology. In accordance with this technology new bitumen binder modified by polymer admixture which has made it possible to capsule bitumen in shell.